Biološki in biomimetski mikroplavalci - Pirc Jevšenak, Vesna (Matrika, 2022)
At small scales and in viscous fluids the effect of inertia is negligible compared to viscosity. Because of that, microscopic biological and artificial swimmers have to adapt with non-reciprocal movement. Precise understanding of the hydrodynamics in these instances has been the goal of many biologists, physicists and engineers for decades and especially in recent years there has been a lot of development of artificial and biomimetic microscopic swimmers with a mind towards biomedical uses.
Keywords: biological microswimmers; biološki mikroplavalci; biomimetic microswimmers; biomimetski mikroplavalci; hidrodinamika; hydrodynamics; microscopic swimmers; mikroplavalci